IDENTIFIKASI JENIS DAN KONDISI POPULASI TUMBUHAN PAKU (Pteridophyta) DI BLOK KOLEKSI TAMAN HUTAN RAYA WAN ABDUL RACHMAN - Savira, Elza Novelia; Indriyanto, Indriyanto; Asmarahman, Ceng (Jurusan Kehutanan, 2021)
Wan Abdul Rachman Forest Park has a collection block, one of which functions to conserve plant species, including ferns (Pteridophyta). This study aims to determine the types of ferns, the population density of each species, and the dominant fern species. The research was carried out by survey using the checkered line method with a sampling intensity of 2%. The area of ​​the collection block is 141.18 ha, the total area of ​​the sample plots is 28,236 or as many as 70 plots.The results identified 16 species of ferns consisting of 3 species of epiphytic ferns, 4 species of epiphytic and terrestrial ferns, and 9 species of terrestrial ferns in forest stand conditions composed of 39 plant species with a density of 1,078.4 individuals/ha.The species of ferns found were Adiantum pediantum, Asplenium pellucidum, Athyrium japonicum, Cyclosorus parasiticus, Davvallia denticulata. Drynaria sparsisora. Thelypteris sp., Stenoclaena polustris, Goniophlebium verrucosum, Leucostalgia pallida, Nephrolepis dicksoniades, Pteris grandifolia, Selliguea deckokii, Diplazium simplivicacium, Pteris mulfida, dan Vittaria elongata. Combination of nail plants of 3333, 57 trees/ha followed by three dominant kinds of Davvallia denticulata, stenoclaena polustris, leucostegia pallida with an INP of 14.55, 11.42 and 10.4. The ferns support in turn is found in plants that support spikes called tangkil (Gnetum gnemon), coconut (Cocos nucifera), randu (Ceiba pentandra), jengkol (Pithecellobium lobatum), jackfruit (Artocarpus heterophyllus), with the dominant form of support called the tangkil (Gnetum gnemon).